If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-15x+-45=-45
We move all terms to the left:
-15x+-45-(-45)=0
We add all the numbers together, and all the variables
-15x=0
x=0/-15
x=0
| -3=-q-1/3 | | 8(d+2)=58–6d | | t=2t+3.59 | | 42x-43=-42x+-43 | | 5x+12x-6=16x+10 | | 2(X–1)+8=4x-20 | | 6=10d-9d | | -9=-3(5+y)+15 | | -6=-6(6+x) | | 7x+4=3×+5 | | 2+5z=62 | | b/2+5=8 | | 7x-10=26+x | | 165-w=228 | | 3n=7n-6 | | m/3+17=19 | | 15=z3+11 | | 4(26+x)=2(17+2x) | | 3a=12-2 | | 48=8(w-5) | | 200+0.25x=382.50 | | 4(2+x)=2(17+2x) | | 4(2+x)=4(17+2x) | | 12m-3=18-9m | | 3s-14=-23 | | 4(2+x)=4(7+2x)+5 | | 12+4u=0 | | 2w-4=0 | | 4(2+x)=2(7+2x) | | 12-4w=0 | | 4(2+x)=4(7+2x) | | 7+-s=10 |